THE REPRESENTATION OF JAPAN DIPLOMACY IDEOLOGY IN JAPAN EMBASSY’ INSTAGRAM SOCIAL MEDIA CONTENT - Asteria Permata Martawijaya; Syihabuddin; Dadang Sudana; Dedi Sutedi (University of Kuningan, 2025)
The proliferation of social media has fundamentally transformed the practice of public diplomacy, with visual platforms like Instagram becoming critical arenas for nations to project strategic narratives and ideological perspectives. This study investigates the representation of Japan's diplomatic ideology through the official Instagram account of a selected Japan Embassy. Employing a Critical Digital Discourse Analysis (CDDA) framework, the research conducts a qualitative, multimodal analysis of visual and textual content to deconstruct the embedded ideological messaging. The findings reveal three dominant, interlocking narratives: (1) the construction of Japan as a Proactive Contributor to Peace, emphasizing normative governance and humanitarian partnership; (2) the ideology of Fusionism, which seamlessly blends traditional heritage with hyper-modern innovation to present a model of balanced societal progress; and (3) the cultivation of Relational Affinity through accessible cultural content and personalized